First Report of Gray Mold in Stringy Stonecrop Caused by Botrytis cinerea - Gyo-Bin Lee; Weon-Dae Cho; Wan-Gyu Kim (한국균학회지)
During a disease survey conducted in March 2024, gray mold symptoms were observed in stringy stonecrop (Sedum sarmentosum) plants grown in vinyl greenhouses in Icheon, Korea. The symptoms included water-soaked lesions and soft rot on the stems and leaves. A large amount of gray mold formed on the lesions during the later stages of disease progression. The gray mold affected 5–20% of the plants in 8 out of 20 surveyed vinyl greenhouses. Three single-conidium fungal isolates were obtained from the lesions and identified as Botrytis cinerea through morphological characterization and phylogenetic analysis. The pathogenicity of the B. cinerea isolates was confirmed by artificial inoculation into stringy stonecrop plants, producing symptoms similar to those observed in the vinyl greenhouses. This is the first report of B. cinerea causing gray mold in stringy stonecrop.